2015
DOI: 10.3233/wor-141945
|View full text |Cite
|
Sign up to set email alerts
|

Severe obesity effect on low back biomechanical stress of manual load lifting

Abstract: In light of previous research on spine, bone and obesity, the study results seem to suggest that severely obese individuals are likely at an increased risk of lifting-related low back pain compared with normal weight individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…Though much remains to be clarified, an increasing body of evidence illuminates the mechanisms underlying the obesity-pain link such as increased loading on joints and spine ( Okifuji & Hare, 2015 ). Higher levels of BMI are also associated with greater wear-and-tear on knee cartilage ( Ding et al, 2005 ), greater disk compression force while lifting ( Singh et al, 2015 ), higher risk for degenerative disk disorders ( Samartzis et al, 2012 ), and altered body mechanics and postures ( Fabris de Souza et al, 2005 ). In particular, overloading on lower back, hip, and knee joints may contribute to structural damage and lead to osteroarthritis ( McVinnie, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though much remains to be clarified, an increasing body of evidence illuminates the mechanisms underlying the obesity-pain link such as increased loading on joints and spine ( Okifuji & Hare, 2015 ). Higher levels of BMI are also associated with greater wear-and-tear on knee cartilage ( Ding et al, 2005 ), greater disk compression force while lifting ( Singh et al, 2015 ), higher risk for degenerative disk disorders ( Samartzis et al, 2012 ), and altered body mechanics and postures ( Fabris de Souza et al, 2005 ). In particular, overloading on lower back, hip, and knee joints may contribute to structural damage and lead to osteroarthritis ( McVinnie, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that there is a threshold of BMI beyond which the development or maintenance of chronic back pain is substantially facilitated. A link between severe obesity and back pain could be explained by a variety of causes including mechanical stresses from excess weight[44], systemic effects from low-grade inflammation from adipose tissue [45], or mediation by other factors such as depression or other chronic conditions. Additional longitudinal studies are still needed to ascertain what component of the obesity-back pain association is due to obesity occurring as a consequence, rather than a cause, of chronic back pain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 72 showed that obese individuals exert significantly greater disk compression force while lifting compared to normal weight individuals, often greatly exceeding the action limit set by the National Institute of Occupational Safety and Health. Thus, it may not be surprising to see that obesity is also related to greater structural damage in the back.…”
Section: Potential Mechanisms Underlying the Obesity–pain Linkmentioning
confidence: 99%